Penggunaan Sistem Pakar dan Algoritma Fuzzy Tsukamoto untuk Mendiagnosis Mucopolysaccharidosis Type II - Iskandar, Agus (Forum Kerjasama Pendidikan Tinggi, 2023)
A rare condition known as Type II mucopolysaccharidosis, often known as Hunter syndrome, is characterized by defective mucopolysaccharide metabolism brought on by a lack of lysosomal enzymes. A class of methanolic illnesses known as MPS type II are inherited in a progressive and recessive way. Organs and tissues are steadily harmed by mucopolysaccharidosis type II (MPS type II). Hence early handling is recommended. Although though it progresses very slowly, the damage brought on by this illness impairs organ function, mental growth, and physical capabilities. A system known as an expert system aims to incorporate human knowledge into computers so that they can solve issues similarly way experts do. The Tsukamoto fuzzy approach, which is highly flexible and has a tolerance for data, was employed in this investigation. It is hoped that this approach will make it easier to determine if the patient has positive MPS type II or negative MPS type II. In this investigation, a value of 0.78 was produced using the Tsukamoto fuzzy method's calculating process